2009
DOI: 10.3201/eid1504.081306
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acquired Toxoplasmosis Caused by Wild Cycle ofToxoplasma gondii, French Guiana

Abstract: From 1998 through 2006, 44 cases of severe primary toxoplasmosis were observed in French Guiana in immunocompetent adults. Toxoplasma gondii isolates exhibited an atypical multilocus genotype. Severe disease in humans may result from poor host adaptation to neotropical zoonotic strains of T. gondii circulating in a forest-based cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
128
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(137 citation statements)
references
References 12 publications
0
128
0
9
Order By: Relevance
“…Compared to the strains of the anthropized environment, the "wild" strains from the Amazonian rainforest in the Guianas exhibited a remarkably high genetic diversity [162,164,165]. Whereas the majority of strains from the adjacent anthropized environment are clustered into a few widespread lineages, the "wild" population of strains does not exhibit any clear genetic clustering/structure nor any linkage disequilibrium, supporting the hypothesis of an important circulation and mixing in this environment.…”
Section: The Wild Environment In Tropical Areasmentioning
confidence: 63%
See 1 more Smart Citation
“…Compared to the strains of the anthropized environment, the "wild" strains from the Amazonian rainforest in the Guianas exhibited a remarkably high genetic diversity [162,164,165]. Whereas the majority of strains from the adjacent anthropized environment are clustered into a few widespread lineages, the "wild" population of strains does not exhibit any clear genetic clustering/structure nor any linkage disequilibrium, supporting the hypothesis of an important circulation and mixing in this environment.…”
Section: The Wild Environment In Tropical Areasmentioning
confidence: 63%
“…This high genetic diversity in tropical wild-life in connection with a sylvatic life cycle has been firstly evoked in French Guiana where severe cases of human toxoplasmosis were detected after eating Amazonian undercooked game or drinking untreated river water [161,162,163]. These cases were due to highly atypical strains, all with unique genotype, as determined by microsatellite analysis [164].…”
Section: The Wild Environment In Tropical Areasmentioning
confidence: 99%
“…were observed in immunocompetent adults (9) . Mercier et al (10) , also in French Guiana, compared T. gondii isolates originating from anthropized suburban areas and from the wild environment and observed that the two environmental populations, wild and anthropized, were genetically well differentiated.…”
Section: Methodsmentioning
confidence: 95%
“…10 Recently, generalized toxoplasmosis in immunocompetent adult human beings caused by strains of T. gondii exhibiting atypical genotypes that were highly virulent in mice has been described. 3,4 Similar atypical genotypes have been isolated from both domestic and wild mammals. 12,13 A 10-year-old male, neutered domestic shorthair cat was referred to the Small Animal Clinic at the University of Bern (Bern, Switzerland) with a 1-week history of anorexia, vomiting, diarrhea, and fever; the symptoms had been unresponsive to treatment with antibiotics (amoxicillinclavulanic acid), nonsteroidal anti-inflammatory drugs (tolfenamic acid), and antiemetics (metoclopramide).…”
mentioning
confidence: 99%